The provision of wage insurance by the firm : evidence from a longitudinal matched employer-employee dataset - Cardoso, Ana Rute (2005)
We evaluate the impact of product market uncertainty on workers wages, addressing the questions: To what extent do firms provide insurance to their workforce, nsulating their wages from shocks in product markets? How does the amount of insurance provided vary with firm and worker attributes? We use a longitudinal matched employer-employee dataset of remarkable quality. The empirical strategy is based on Guiso et al. (2005). We first estimate dynamic models of sales and wages to retrieve consistent estimates of shocks to firms’ sales and to workers’ earnings. We are then able to estimate the sensitivity of wages to permanent and transitory shocks to firm performance. Results point to the rejection of the full insurance hypothesis. Workers’ wages respond to permanent shocks to firm performance, whereas they are not sensitive to transitory shocks. Managers are not fully insured against transitory shocks, while they receive the same protection against permanent shocks as workers in other occupations. Firms with higher variability in their sales, and those operating in different industries, offer more insurance against permanent shocks. Comparison with Guiso et al. (2005) indicates that Portuguese firms provide less insurance than Italian firms, corroborating evidence on the high degree of wage flexibility in Portugal.